2014
DOI: 10.1111/tgis.12076
|View full text |Cite
|
Sign up to set email alerts
|

Detecting and Analyzing Mobility Hotspots using Surface Networks

Abstract: Capabilities for collecting and storing data on mobile objects have increased dramatically over the past few decades. A persistent difficulty is summarizing large collections of mobile objects. This article develops methods for extracting and analyzing hotspots or locations with relatively high levels of mobility activity. We use kernel density estimation (KDE) to convert a large collection of mobile objects into a smooth, continuous surface. We then develop a topological algorithm to extract critical geometri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 54 publications
2
41
0
Order By: Relevance
“…Several methods have been proposed to identify hot crime areas in current literature (Chainey et al, 2008;Ratcliffe, 2010;Hu et al, 2014). These approaches include spatial ellipses, thematic mapping of administrative units, grid thematic mapping, and kernel density estimation (KDE) (Chainey et al, 2008;Ratcliffe, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Several methods have been proposed to identify hot crime areas in current literature (Chainey et al, 2008;Ratcliffe, 2010;Hu et al, 2014). These approaches include spatial ellipses, thematic mapping of administrative units, grid thematic mapping, and kernel density estimation (KDE) (Chainey et al, 2008;Ratcliffe, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Among all the existing methods, KDE is the most popular one for its ability to discover different shapes of hot areas. In a KDE surface, the areas with high values over the threshold are identified as hot areas (Hu et al, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Orlandini, Moretti, and Gavioli (2014) for analytical representation and 495 Mower (2009) for visualization have re-examined the role of slope lines as used in the original work. Hu, Miller, and Li (2014) have shown that surface network theory has use in the hotspot analysis of mobile objects, such as vehicles in traffic or potentially diffusion of 500 disease in a populace. Wolf (2014) has examined the use of the surface network in nanotechnology.…”
Section: Contemporary Research On the Surface Network 480mentioning
confidence: 99%
“…Taxi cab trajectory data recorded in April 2015 are used to present the average taxi mobility trends and evaluate travel time predictability. Commonly seen mobility research often focuses on the mobility patterns of independent individuals (person or vehicle) based on such as mobile phone data [22,30,31] and GPS data [22,32,33]. Differently, travel time predictability emphasizes the expected success rate of travel time prediction based on a given travel time series from individual or statistics values of travel time, and the statistical trends of travel times from multiple vehicles may present traffic patterns more effectively than individual mobility which may be affected by unpredictable driving behaviors.…”
Section: Introductionmentioning
confidence: 99%